Panhypopituitarism with empty sella a sequel of pituitary hyperplasia due to chronic primary hypothyroidism - Dutta, Deep (Medknow Publications & Media Pvt Ltd, 2012)
Asymptomatic reversible pituitary hyperplasia is common in patients with untreated primary hypothyroidism. Occurrence of empty sella (ES) in this scenario is extremely rare (only three reports till the date) and panhypopituitarism has not been reported in such patients. We report a 27 year man with severe short stature (height-133 cm; standard deviation score-7.36) and delayed puberty who had symptoms suggestive of hypothyroidism along with chronic persistent headache since 6 years of age. Pituitary imaging done for headache at 11 years age showed pituitary hyperplasia. He was diagnosed of primary hypothyroidism for the 1(st) time at 21 year age, a diagnosis which was likely missed for 15 years. Levothyroxine therapy leads to resolution of all symptoms and a height gain of 28 cm over last 6 years. Evaluation for lack of progression of puberty along with chronic nausea, vomiting, fatigue and weight loss for the last 1 year revealed secondary hypocortisolism (9 am cortisol-4.8 mcg/dl; ACTH-3.2 pg/ml), growth hormone deficiency (IGF-1: 65 ng/ml; normal: 117-325 ng/ml) and hypogonadotrophic hypogonadism (9 am testosterone: 98 ng/dl; [280-1500] LH-0.01 mIU/L [1.14-5.75]) with ES on magnetic resonance imaging (MRI) brain. Uncontrolled thyrotroph hyperplasia due to chronic untreated primary hypothyroidism for 15 years may have been damaging the adjacent corticotrophs, somatotrophs and gonadotrophs resulting in panhypopituitarism and empty sella. This is perhaps the first report of panhypopituitarism with empty sella syndrome developing in a patient with pituitary hyperplasia, a sequel of chronic untreated primary hypothyroidism.